Analisis Fiqh Siyasah Tanfidziyyah Terhadap Implementasi Kebijakan Pencegahan dan Penanganan Kekerasan Seksual di Perguruan Tinggi (Studi UIN Raden Intan Lampung) - Liza; Maimun; Frenki (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2025)
This study aims to analyze the implementation of Article 6 paragraph 3 of Permendikbudristek Number 30 of 2021 concerning the prevention and handling of sexual violence in higher education institutions through the perspective of Fiqh Siyasah Tanfidziyyah, with a focus on studies at the Raden Intan State Islamic University (UIN) Lampung. This study is motivated by the urgency of protecting victims of sexual violence and the need to strengthen a responsive, fair, and Islamic law-based handling system. The method used is empirical juridical with a qualitative approach. Data was obtained through relevant laws and regulations, field observations, in-depth interviews with campus bureaucrats, the PPKS/PSGA task force, LKBH, students, and analysis of official policy implementation documents. The findings show that UIN Raden Intan Lampung has implemented progressive policies for the prevention and handling of sexual violence, in line with Article 6 paragraph 3 of Permendikbudristek No. 30 of 2021. From the perspective of Fiqh Siyasah Tanfidziyyah, this policy reflects the exercise of administrative authority by the campus as wali al-amr, which aims to maintain the welfare and honor of the academic community. The implementation of this policy demonstrates the integration of positive norms and sharia values, particularly in efforts to prevent harm (mafsadah) and realize the protection of human rights in the context of higher education.